Assessment of Working Environment Factors Influencing Construction Workers' Performance in the Nigerian Construction Industry - Ihedigbo, Kingsley Sunday; Awwal, Hamzat Mohammed; Sakiru, Rasaq Ademola; Olughu, Christopher Egwu; Bello, Abdulkabir Opeyemi (Journal of Sustainability and Environmental Management, 2023)
The working environment plays a crucial role in determining the performance of employees in the construction industry. Factors such as physical conditions, ergonomics, and the social and cultural atmosphere significantly impact how well employees carry out their tasks. Unfortunately, these factors have been negatively affecting the performance and productivity of the Nigerian construction industry. This study aims to assess the working environment factors that influence construction workers' performance in Nigeria. A quantitative research approach was adopted, utilizing a five-point Likert-based questionnaire for data collection. A total of 200 questionnaires were distributed, resulting in 187 valid responses, which is considered adequate for analysis. The results indicate that 11 out of the 16 hypothesized barriers were statistically significant, surpassing the set threshold of 3.5. The most significant factors influencing construction workers' performance in the working environment were found to be disputes among workers, poor weather conditions, equipment failure, changes in orders during unpredictable execution, and major rework due to unforeseen conditions. Through factor analysis, the barriers were categorized into three components: "Physical and Social-related barriers," "Operational-related barriers," and "Welfare-related barriers." This study highlights the paramount importance of working conditions in determining employee performance and recommends the development and implementation of strategies to mitigate working condition challenges in the construction industry. The findings of this study can be applicable to construction industries in other countries with similar characteristics to Nigeria.